Prevalence and Risk Factors for Postpartum Depression in Different Birth Settings: A Prospective Study - Jai Dev Maheshwari, Aftab Hussain Abro, Nargis Gulab, Sadia Kanwal, Amna Najam, Amna Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum depression (PPD) significantly affects maternal and child health, with various risk factors influencing its prevalence. Understanding PPD across different birth settings and associated factors is essential for targeted intervention. Objective: To determine the prevalence of postpartum depression (PPD) and identify its associated risk factors across different birth settings. Material and Methods: This prospective study included 345 postpartum mothers at Department of Gynaecology and Obstetrics Northwest school of medicine Hayatabad Peshawar , from October to March 2023. Data were collected via a structured questionnaire, including demographic, socioeconomic, and clinical variables, and the Edinburgh Postnatal Depression Scale (EPDS) was used to screen for PPD. Key variables included birth setting (hospital, birthing center, home), mode of delivery, age, education level, socioeconomic status, employment status, and history of depression or anxiety. Statistical analyses were conducted using Chi-square tests to examine associations, with a significance level of p ≤ 0.05. Results: PPD was present in 37% (127 out of 345) of participants. A significant association was found between birth setting and PPD, with home births having the highest prevalence (58.3%) compared to hospitals (31.6%) (p = 0.001). No significant associations were observed for mode of delivery (p = 0.398) or prior mental health history (p = 0.210). Sociodemographic factors, including age, socioeconomic status, and employment, were also not significantly associated with PPD. Conclusion: Birth setting was significantly associated with PPD, highlighting the importance of supportive hospital environments in potentially reducing PPD risk. Further research is needed to explore specific interventions for high-risk groups, particularly in non-hospital birth settings. Keywords: Postpartum depression, birth setting, maternal mental health, risk factors, Edinburgh Postnatal Depression Scale (EPDS), sociodemographic factors